Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1046/j.1365-2710.1997.94975949.x
|View full text |Cite
|
Sign up to set email alerts
|

The gift relationship between pharmaceutical companies and physicians: an exploratory survey of physicians

Abstract: The purpose of this exploratory study was to survey physicians' attitudes surrounding the 'gift relationship' between pharmaceutical companies and physicians. A survey was mailed to 1000 randomly selected West Virginia physicians, of which 283 (28.3%) responses were received. The most commonly received gifts reported by the study physicians were trinkets (77.4%), followed by books (41.7%) and meals (41%). Principal component analysis and varimax rotation identified seven physician belief constructs. The mean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 8 publications
1
22
1
1
Order By: Relevance
“…Note, that crucially, the advertising and bribing motives for gifts are not mutually exclusive. 27 The discrepancy between in ‡uence on self and in ‡uence on most other physicians is corroborated by [Madhavan et. al., 1997].…”
Section: Resultsmentioning
confidence: 91%
“…Note, that crucially, the advertising and bribing motives for gifts are not mutually exclusive. 27 The discrepancy between in ‡uence on self and in ‡uence on most other physicians is corroborated by [Madhavan et. al., 1997].…”
Section: Resultsmentioning
confidence: 91%
“…Physicians variably rated the informational value of PRs in medical education [1][3], [5]–[8], [10], [12], [15][18]. Their beliefs about the influence of interactions with PRs on prescribing behaviors were mixed [1], [3], [5]–[8], [10], [13], [14], [16], [18], [19]. They believed that their colleagues were more likely to be influenced than themselves [13], [14], [16], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Their beliefs about the influence of interactions with PRs on prescribing behaviors were mixed [1], [3], [5]–[8], [10], [13], [14], [16], [18], [19]. They believed that their colleagues were more likely to be influenced than themselves [13], [14], [16], [19]. Physicians tended to believe that it was appropriate to receive inexpensive gifts [2], [6], [8], [14], [16], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…36 Several studies have shown that physicians deny industry's influence. 5,[37][38][39][40][41][42][43] However, research shows a strong correlation between receiving industry benefits and favoring their products. 7,8,44 Physicians and residents feel they are immune to the promotional activities.…”
Section: Discussionmentioning
confidence: 99%